Going the Extra Mile Because My Organization Does: How Does Corporate Social Responsibility Influence Organizational Citizenship in Nigeria?. (February 2020) - Onyishi, Ike E.; Amaeshi, Kenneth; Ugwu, Fabian O.; Enwereuzor, Ibeawuchi K.
ABSTRACT: There is a growing call to understand the influence of corporate social responsibility (CSR) on organizational outcomes, especially in developing economies. Given the strong link between organizational citizenship behavior (OCB) and organizational performance and survival, on one hand, and the constant need in the literature to understand their antecedents, on the other hand, this study adopts the social cognitive theory to examine the relationship between employees' perceptions of their organizations' engagement in CSR and their individual engagement in OCB in Nigeria. Based on the relevance of organizational learning culture to both CSR and OCB, the study further examines the mediating role of organizational learning culture in the relationship between employees' perceptions of their organization's CSR engagement and their individual engagement in OCB. We tested these relationships in a sample of 254 employees drawn from banking, oil and gas, manufacturing and service industries. The results showed that there is a significant positive relationship between employees' perceptions of their organizations' engagement in CSR and their exhibition of OCB. This relationship is mediated by organizational learning culture. The implications of the results for CSR, especially in non-enabling institutional contexts, were discussed.